2021
DOI: 10.3389/fbioe.2021.644014
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles as a Strategy in the Fight Against Multi-Resistant Salmonella enterica Isolated From Dairy Calves

Abstract: Infectious diseases are one of the most important health problems worldwide, one of the main causes being the development of multi-resistant microorganisms. Likewise, the zoonotic potential of some pathogens and their ability to transfer resistance mechanisms, reduce the therapeutic options in both humans and animals. Salmonella enterica is an important pathogen that affects a wide range of animal species and humans, being Salmonella Typhimurium one of the most frequent serotypes affecting cattle, causing ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Due to the interfering effect of salt, the limitations of the usefulness of silver and silver derivatives are overcome by the use of Ag nanoparticles against microorganisms, which have been proven to be effective antibacterial agents (Estevez et al, 2021). Antimicrobial activity was also found in the biosynthetic AgNPs against all the test organisms used in this study.…”
Section: Discussionmentioning
confidence: 74%
“…Due to the interfering effect of salt, the limitations of the usefulness of silver and silver derivatives are overcome by the use of Ag nanoparticles against microorganisms, which have been proven to be effective antibacterial agents (Estevez et al, 2021). Antimicrobial activity was also found in the biosynthetic AgNPs against all the test organisms used in this study.…”
Section: Discussionmentioning
confidence: 74%
“…A greater bactericidal and bacteriostatic effect of biologically synthesized Ag NPs, concerning the solution of silver nitrate, the precursor of these nanoparticles, was found against multidrug-resistant strains of Salmonella Typhimurium , isolated from animals with diarrhea and septicemia. This highlights the potential application of Ag NPs as an alternative against multidrug-resistant strains [ 23 ]. At the concentration of 25 μg mL −1 , Ag NPs completely inhibited the Salmonella strain, proving an effective antibacterial potential [ 24 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…It is shown that the antibacterial properties of PMMA materials can be improved by adding nano-Ag-ZrP to PMMA materials. The presumed antibacterial mechanism may be attributed to direct contact between AgNP and the bacterial cell membrane, Ag + release, bacterial cell wall and cell membrane disruption, reactive oxygen species (ROS) generation, bacterial substance leakage, and subsequent bacterial internal structure obliteration, culminating in a bactericidal effect (Ji et al, 2020;Hajipour et al, 2012;Dakal et al, 2016;Estevez et al, 2021). The staining results of S. mutans and E. coli on the surface of each group of specimens.…”
Section: Effect Of Nano-ag-zrp On Antibacterial Properties Of Room-te...mentioning
confidence: 99%